El código Davinci / Ron Howard - Howard, Ron, 1954- (Columbia pictures, 2006)
A murder inside the Louvre, and clues in Da Vinci paintings, lead to the discovery of a religious mystery protected by a secret society for two thousand years, which could shake the foundations of Christianity.